Professionele gevormdheid van die verpleegkundige - die beeld van die beroep na buite - W. Kotzé (AOSIS, 1982)
The degree of professionalism of a group determines the image which it projects. There are two types of nurses - those who are dedicated to nursing as a career and those for whom nursing is merely a job. The latter group inhibits professional development and the reason for their existence can be sought in two areas - firstly their initial attitude and disposition and secondly the opportunities which were provided for socialisation and professionalisation during their training. A professional person exhibits specific characteristics and to ensure a high degree of professionalism in nursing it is necessary to: - select student nurses with care and according to predetermined criteria; - use all opportunities to build positive attitudes; - help students to develop an insight into professional affairs and the meaning and demands of professionalism by emphasising these aspects throughout training.